2001
DOI: 10.1002/1521-3773(20010903)40:17<3228::aid-anie3228>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Carbon Monoxide and Imines as Peptide Derivative Synthons: A Facile Palladium-Catalyzed Synthesis ofα-Amino Acid Derived Imidazolines

Abstract: One of the most facile routes to prepare carboxylate‐substituted imidazolines is by the palladium‐catalyzed coupling of an imine, carbon monoxide, and an acid chloride. In this reaction, a peptide unit is constructed and directly incorporated into the heterocyclic core (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 38 publications
0
51
0
Order By: Relevance
“…So far, some progress on the development of efficient synthetic approaches to these products has been made in the past several decades (6)(7)(8)(9)(10)(11)(12)(13)(14)(15), but it is still an active and challenging topic in synthetic organic chemistry.…”
mentioning
confidence: 99%
“…So far, some progress on the development of efficient synthetic approaches to these products has been made in the past several decades (6)(7)(8)(9)(10)(11)(12)(13)(14)(15), but it is still an active and challenging topic in synthetic organic chemistry.…”
mentioning
confidence: 99%
“…By means of mesoionic 1,3‐oxazolium‐5‐oxide (i.e münchnones) as a reaction intermediate, the research group of Arndtsen developed a series of MCRs involving palladium‐catalyzed carbonylation. The core of these CMCRs lies in a simple and general protocol for the carbonylative synthesis of mesoionic 1,3‐oxazolium‐5‐oxides . The generation of these oxides proceeds through the formation of a palladacycle by the oxidative addition of an N ‐acyliminium salt to Pd 0 , the coordination and insertion of carbon monoxide, and β‐hydride elimination (Figure ).…”
Section: Palladium‐catalyzed Cmcrsmentioning
confidence: 99%
“…Because there is an equilibrium between mesoionic 1,3‐oxazolium‐5‐oxide and its electrophilic ketene isomer, several different kinds of reactions (e.g., 1,3‐dipolar cycloaddition, [2+2] cycloaddition, or nucleophilic addition) can occur on the oxide. By employing an appropriate substrate as the fourth component, Arndtsen's group successively achieved the synthesis of α‐amino acid derivatives, β‐lactams, imidazolines, imidazolinium salts, and pyrroles (Scheme a). Through the transmetallation of the palladacycle with an organotin reagent, reductive elimination, and work‐up with ammonium acetate, the carbonylative five‐component synthesis of imidazolones was also achieved (Scheme b) …”
Section: Palladium‐catalyzed Cmcrsmentioning
confidence: 99%
“…The palladium-mediated synthesis of imidazolines reported by Arndtsen can be held in this category [48]. Within this context, the group of Harwood reported that chiral azomethine ylides 61 generated in situ from (5S)-phenylmorpholin-2-one 59 in the presence of aromatic aldimines 60 and pyridinium p-toluenesulfonate can undergo cycloaddition with excess of imine to give imidazolidines 62 as single products.…”
Section: Through Cyclic Intermediatesmentioning
confidence: 99%